A regência verbal em livros didáticos de língua portuguesa dos anos finais do ensino fundamental - Rabelo, Junes da Silva (2024)
The process of teaching and learning grammar has been a difficult task for both teachers and basic education students. The teaching of verbal regency, as a grammatical content, is not part of this reality. In this education endeavor, teachers and students have an importantally, the Portuguese language textbook, but which, at times, does not meet all the expected needs for this process to occur without harm. In view of this, in this research, with a qualitative-quantitative and descriptive approach, we proposed to investigate the approach to verbal regency in Portuguese Language textbooks for Elementary School final years approved in the National Textbook Program (PNLD) 2024 – 2027, which are: from the publisher Moderna [Araribá Conecta – Português; Novo Singular & Plural: Leitura, Produção e Estudos de Linguagem; Se Liga na Língua: Leitura, Produção de Texto e Linguagem; SuperAÇÃO! Português]; from the publisher FTD [A Conquista - Língua Portuguesa, Trajetórias - Língua Portuguesa]; fromthepublisher Saraiva [Jornadas Novos Caminhos – Língua Portuguesa, Português Linguagens]; from the publisher Ática [Teláris Essencial – Língua Portuguesa]; from the publisher SEI [Metaverso - Língua Portuguesa]; from the publisher SM [Geração Alpha - Língua Portuguesa].To support the theoretical discussion, we present the concept of grammar according to Possenti (1996), Travaglia (1998 [1996]) and Franchi (2006). Wealso show the guidelines on teaching grammar in the Parâmetros Curriculares Nacional (PCN), in the Base Nacional Comum Curricular (BNCC) and the linguistic bias of Functionalism. We also high light the definition of verbal regency according to Traditional Grammar and Valencian Grammar, in addition to exposing considerations about teaching this linguistic content from the perspective of Travaglia (2003). When analyzing the collections, we noticed that most of them do not satisfactorily address the topic of verbal conducting, as there are gaps. In this sense, as anout come of this research, weproposed a didactic notebook, whose didactic-pedagogical activities are focused on the functioning and reflection of verbal regency, related to the effect and change of meaning in the verb plus complement relationship, to the analysis of verbal regency in language Portuguese based on the standard normand its variations, depending on the three axes for teaching grammar, by Vieira (2018 [2013]).